Influence of coating on the photoluminescence of Tb3＋ doped ZnSe/ZnS core-shell quantum dots - Cichos, J.; Karbowiak, M.; Hreniak, D.; Stręk, W. (Journal of rare earths, 2016)
Tb3＋-doped ZnSe and ZnSe/ZnS nanocrystals were synthesized using modified hot-injection method. The observation of the characteristic quantum dots absorption features in a time-gated excitation spectrum was recorded while monitoring Tb3＋ emission at 545 nm provided direct evidence for successful incorporation of dopant ions into semiconductor host. Relatively long decay time （-1.5 ms） of Tb3＋ emission indicated that dopant ions were well protected from interaction with surface ligands. Emission properties of core ZnSe：Tb3＋ nanocrystals were only slightly modified upon growth of ZnS shell.